Ideological rhetoric: a critical discourse analysis of Prabowo’s first inauguration speech - Hariati, Puji; Purwarno, Purwarno (UNIB Press, 2025)
This study examines the rhetorical strategies, ideological rhetoric, and political ideology of nation-building presented by Prabowo Subianto in his inauguration speech as the newly elected president of Indonesia on October 20, 2024. Using a descriptive qualitative approach, the analysis is grounded in Critical Discourse Analysis (CDA) to reveal the underlying rhetorical devices and ideological themes conveyed in his speech. The study is structured through two interlinked dimensions: rhetorical strategies and ideological rhetoric, utilizing Aristotle’s rhetorical concepts of ethos, pathos, and logos to provide a comprehensive interpretation of the speech. The analysis addresses key themes such as sovereignty, the relationship between the state and its citizens, justice, equality, the vision of a